Real-time Ultraviolet Radiation Sensor Based on Modified Cladding Optical Fibers Technology - Muhammed, Nadia F.; Mahmood, Aseel I.; Kadhim, Shehab A.; Naseef, Intisar A.; Jabor, Ashwaq A.; Azzawi, Mohanad M. (Iraqi Journal of Science, 2021)
In this work, the performance of single-mode optical fibers (SMFs) for ultraviolet (UV) radiation monitoring and dosimetry applications is presented. In particular, this work will focus on the Radiation-Induced Absorption (RIA) phenomena in the Near-Infrared domain (NIR). Such phenomena play a very important role in the sensing mechanism for SMF. Single mode fibers with a diameter of 50 µm were used for this purpose. These fibers were dipped into germanium (Ge) solution with different concentrations (1, 3, and 5 wt%) to produce the sensing part of the sensor. For all optical fiber sensors under investigation, the results indicated the dependence of the RIA on the applied UV radiation energy. Also, a redshift in peak wavelength was obtained. The influence of Ge concentration on sensing efficiency was studied and the best results were obtained with 3 wt% concentration as compared to 1 wt % and 5 wt % concentrations. The presented sensor shows good sensitivity to UV radiation which makes it possible to be applied in medical applications.